Metastasectomy as optimal treatment for late relapsing solitary brain metastasis from testicular germ cell tumor: a case report - Iida, Keitaro (BMC Res Notes, 2014)
BACKGROUND: Management of late relapse of a testicular germ cell tumor is difficult because few cases have been reported and the tumors are intractable to chemotherapy. Here we present a case with a single brain metastasis from late relapse of a testicular germ cell tumor. This is the first report of a brain metastasis that was treated successfully only by surgery. CASE PRESENTATION: A 19-year-old Japanese man presented with breathing difficulties and left testis enlargement and he was diagnosed with a yolk sac tumor following a left orchiectomy. At the time of diagnosis, multiple lung metastases were apparent on computed tomography, and serum alpha-fetoprotein level was elevated to 10,245 ng/ml. The patient received three postoperative courses of bleomycin, etoposide and cisplatin and etoposide and cisplatin respectively and a complete response was obtained. Four years after surgery, the patient was admitted to the hospital due to a sudden seizure. High alpha-fetoprotein levels (539 ng/ml) were evident and magnetic resonance imaging suggested a 45-mm single brain tumor in the right parietal lobe, for which surgery was performed. The pathological diagnosis was yolk sac tumor. The alpha-fetoprotein level remained normal at 2 months after operation. There was no recurrence 24 months post-operation. CONCLUSION: Chemoresistance and late neurotoxicity are concerns in treating brain metastasis with chemotherapy or cerebral radiotherapy. Surgery is believed to be the optimal treatment choice if the size of the brain metastasis is larger than 35-mm and the late relapse area is surgically accessible.